Preparation and swelling of polymeric absorbent containing hydroxamic acid group from polymer grafted sago starch - Lutfor, M.R.; Sidik, S.; Wan Yunus, W.M.Z.; Ab Rahman, M.Z.; Mansoor, A.; Jelas, H. (Elsevier, 2001)
Poly(methyl acrylate) (PMA) grafted sago starch was prepared from the reaction between methyl acrylate and sago starch by free radical initiating process in which ceric ammonium nitrate (CAN) was used as an initiator. The common procedure was used to prepare a new polymer containing hydroxamic acid functional group from PMA grafted sago starch and hydroxylamine under alkaline solution. The PMA grafted sago starch and poly(hydroxamic acid) was characterized by FT-IR spectroscopy. The water absorbency or swelling of the poly (hydroxamic acid) absorbent was measured as a function of different sago starch concentration in absorbent. It was observed that the swelling in distilled water and various salt solutions increases with decreasing sago starch concentration. The maximum absorbency in water was 192 g water g-1 at 31% sago starch content in absorbent. The absorbency in the various salt solutions decreases with the increasing salt concentration in solution. At the same salt concentration in solution, the swelling has the following tendency: Na+>Ca2+>Fe3+.